Historical Interpretation of the Past: The Way of Mental Enslavement or Liberation? - Mandryk-Melnychuk, M.; Kotsur, A.; Sharavara, T. (Український історичний журнал, 2020)
The purpose of this study is to find out the role of a professional researcher in historical interpretation of the past, to analyze projected threats that deal with speculation of historical facts, events, their arbitrary use, deliberate distortion of them for the formation of historical and social memory. The research methodology. The research is based on the principles of historicism, comprehensiveness, objectivity and systemacity. General scientific methods of analysis, synthesis, generalization, specialhistorical (retrospective, comparative, problem-chronological), as well as the method of interdisciplinary and polydisciplinary synthesis are used in the presentation of the material. The scientific novelty. The roles that a professional researcher of the past can play – from the propaganda of hostile ideas, selective interpretation of sources, speculation on a certain topic – to an impartial re-enactor, a competent expert are analyzed. It is proved that suppression or deliberate distortion of particular pages of history, or their excessive ideologization, which was actively practiced in the Soviet science, equates with political violence, the manipulation of the consciousness of entire communities and generations. The use of such approaches has always been destructive in nature for researchers, who fulfilled the functions unusual to them, and for society, which, because of ignorance of its own past, is losing the vision of its future now. Conclusions. Consequently, manipulations with the interpretation of the past – different understanding of the same milestone events, excessive politicization of them, promotion of the enemy’s image, deliberate emphasis on human emotions, ideological layers associated with a particular page of people’s life – have an irreversible impact on the formation of social memory of Ukrainians. These factors contribute to deepening the processes of disintegration of society and indirectly strike at the foundations of nationhood. Мета дослідження полягає у з’ясуванні ролі професійного дослідника в історичній інтерпретації минулого, аналізі ймовірних загроз, які несе у собі спекуляція історичними фактами, подіями, довільне оперування ними, навмисне їх перекручення для формування історичної та соціальної пам’яті. Методологія. Дослідження ґрунтується на принципах історизму, усебічності, об’єктивності, системності. При викладенні матеріалу застосовано загальнонаукові методи аналізу, синтезу, узагальнення, спеціально-історичні (ретроспективний, порівняльний, проблемно-хронологічний), а також метод міждисциплінарного та полідисциплінарного синтезу. Наукова новизна. Проаналізовано ролі, які може відігравати фаховий дослідник минулого – від пропаґанди ворожих ідей, вибіркового тлумачення джерел, спекулювання на певній тематиці до неупередженого реконструктора історії, компетентного експерта. Доведено, що замовчування або свідоме спотворення окремих сторінок історії, надмірна їх ідеологізація, що активно практикувалося в радянській науці, прирівнюється до політичного насильства, маніпуляції свідомістю цілих спільнот і поколінь. Застосування таких підходів завжди мало руйнівний характер як для самих дослідників, які виконували невластиві їм ролі, так і для суспільства, котре через незнання власного минулого втрачає візію свого майбутнього. Висновки. Маніпуляції з тлумаченням минулого – різне розуміння одних і тих самих знакових подій, надмірна їх політизація, розкручування образу ворога, навмисне акцентування на людських емоціях, ідеологічні нашарування, пов’язані з тієї чи іншою сторінкою життя народу – мають незворотний вплив на формування соціальної пам’яті. Ці чинники сприяють поглибленню процесів дезінтеґрації суспільства й опосередковано розхитують підвалини державності.